Intimate partner violence among undergraduate students of two universities of the state of São Paulo, Brazil - Tânia Aldrighi Flake; Claudia Barros; Lilia B. Schraiber; Paulo Rossi Menezes (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
INTRODUCTION: The prevalence of violence in intimate relationships, suffered or perpetrated, was estimated among undergraduate students, be it physical, psychological and sexual, describing the overlap between them. This is an original study and there is scarce literature on this matter in Brazil. Men and women were investigated and some issues on gender violence were discussed. METHODS: The study is part of the multicenter survey "International Study of Violence in Dating - IDVS" conducted in 2002 - 2003, using its standardized instrument. A total of 362 students, from two universities in the state of São Paulo, one public and one private, answered the self-reported questionnaire, being 37% male and 63% female, mean age of 20 years old. Suffered and perpetrated intimate partner violence during life was examined. RESULTS: Among all interviewees, 75.9% suffered and 76.4% perpetrated some kind of violence throughout life. Psychological violence was the most prevalent type, followed by sexual violence, both suffered and perpetrated. The great superposition between suffered and perpetrated violence (83.9%) reflects the reciprocity of aggression, with no observed difference between men and women. The results of this study are consistent with previous literature on dating violence, which shows high prevalence of suffered and perpetrated violence, besides reciprocity for both men and women. CONCLUSIONS: Intervention actions at this stage of intimate relationships may potentially impact on subsequent marital partnership situations.